Enhanced flow boiling heat transfer from 3D printed substrates - Chua, Barnabas Wei Li (2016)
Ever since Moore's law earned its place as an annual target for the semiconductor industry, it is evident that the exponential surge in circuit density is not exempted from huge increase in heat flux. Thus, the need to manage heat transfer is crucial as we expect heat dissipation to rise along with the increase in transistor count. This project seeks to study techniques and parameters which contribute to enhanced flow boiling heat transfer, in search for improved thermal management.